Gas sensor, application thereof and method for detecting H2S concentration in gas

By using three-dimensional graphene/metal oxide composite spheres in gas sensors and using the Joule effect for self-heating, the existing gas sensors have been solved, and a high sensitivity, low power consumption and portable gas sensors are achieved.

CN119595714AActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311166872.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

Existing gas sensors have low sensitivity and slow response at room temperature and require high temperature operation to reduce the conductivity of metal oxides, resulting in high power consumption and unsuitable for miniaturization and long-term use.

Method used

Three-dimensional graphene/metal oxide composite spheres are used to connect to the pins of the ceramic package through wires, and self-heating is used to reduce sensor power consumption, and gas-sensitive performance is improved through multi-stage channel structure and high specific surface area.

Benefits of technology

It realizes the improvement of the sensitivity and response speed of the gas sensor under room temperature conditions, reduces power consumption, and is suitable for miniaturization and portable applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119595714A_ABST
    Figure CN119595714A_ABST
Patent Text Reader

Abstract

The invention relates to the field of materials, and discloses a gas sensor and application thereof.The gas sensor comprises a ceramic package and a three-dimensional graphene / metal oxide composite ball arranged in a groove of the ceramic package in a suspended mode, the three-dimensional graphene / metal oxide composite balls are connected with the pins of the ceramic package through wires; the three-dimensional graphene / metal oxide composite pellet comprises a graphene pellet and a metal oxide loaded on the graphene pellet; the specific surface area of the three-dimensional graphene / metal oxide composite sphere is 50-500m < 2 > / g. The gas sensor is based on the Joule principle, the working temperature and the power consumption of the sensor are reduced by utilizing the three-dimensional structure and the synergistic effect of the three-dimensional graphene / metal oxide composite spheres, low-power-consumption gas detection is realized, miniaturization and portability of the sensor are facilitated, and the gas sensor is very suitable for being applied to the field of gas monitoring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials, and in particular to a gas sensor and application thereof. Background Art

[0002] In recent years, as people's attention to the environment, safety and health has gradually increased, research on gas sensors that can accurately monitor toxic and harmful gases has also begun to heat up. As a widely used gas sensor, resistive gas sensors can convert gas concentration signals into electrical signals through the resistance changes generated by the reaction between oxygen anions on the device surface and the target gas, thereby monitoring and analyzing the concentration of toxic and harmful gases. Common gas-sensitive materials used to prepare resistive gas sensors are nano-metal oxides, including nano-iron trioxide (Fe 2 O 3 ), tin dioxide (SnO 2 ), tungsten trioxide (WO 3 ), molybdenum trioxide (MoO 3 ), copper oxide (CuO), zinc oxide (ZnO), etc. However, due to the disadvantage of low room temperature conductivity of metal oxides, metal oxide-based gas sensors need to be heated to 200-400°C to work properly. According to statistics, nearly 60% of the energy of the sensor is used to heat the sensing material, which not only increases energy consumption, but also is not conducive to the miniaturization and long-term use of the sensor, and also brings safety hazards. Therefore, how to prepare sensors with low energy consumption and excellent gas-sensitive performance has become one of the research hotspots in the field of gas sensors in recent years. Therefore, it is necessary to compound it with nano-precious metals, nano-carbon materials, conductive polymers, etc. to lower its operating temperature and reduce power consumption. Among them, graphene, with its excellent conductivity (conductivity reaches 108S·m -1 ), thermal conductivity (thermal conductivity can reach 5300W·m -1 K -1 ), mechanical properties (Young's modulus reaches 1TPa) and large specific surface area (2630m 2 g -1 ), becoming one of the hot topics in the research of nano gas-sensitive materials.

[0003] Common graphene materials can be divided into one-dimensional nanofibers, two-dimensional nanofilms and three-dimensional graphene spheres according to their dimensions. The porous structure of three-dimensional graphene spheres is very beneficial for improving their adsorption, energy storage, and gas-sensing properties. First, the three-dimensional structure can effectively reduce the stacking of graphene sheets, which is conducive to maintaining the advantage of high specific surface area of ​​graphene and increasing the active sites of the reaction; secondly, the interconnected channels make it easier for molecules to diffuse into the material, improving its sensitivity; finally, the three-dimensional graphene skeleton not only provides support sites for the loading of other nanomaterials, but also speeds up the flow of electrons inside the material and enhances its conductivity. Combining three-dimensional graphene with nano-metal oxides can achieve complementary advantages of the two, while using heterojunctions and synergistic effects to further enhance their gas-sensing properties and expand their application range.

[0004] However, the current three-dimensional graphene / metal oxide gas sensors have high activation energy for reacting with target gases at room temperature, resulting in low sensitivity and slow response speed, which cannot meet people's needs in real life. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of low sensitivity, slow response speed, high operating temperature and high power consumption of existing gas sensors at room temperature, and to provide a gas sensor and its application. The invention reduces the power consumption of the sensor through the Joule effect, which is conducive to the miniaturization and portability of the sensor.

[0006] In order to achieve the above-mentioned object, the present invention provides a gas sensor on one hand, which includes a ceramic package and a three-dimensional graphene / metal oxide composite ball suspended in a groove of the ceramic package, and the three-dimensional graphene / metal oxide composite ball is connected to the pin of the ceramic package through a wire;

[0007] The three-dimensional graphene / metal oxide composite spheres include graphene spheres and metal oxides supported on the graphene spheres;

[0008] The specific surface area of ​​the three-dimensional graphene / metal oxide composite sphere is 50-500m 2 / g.

[0009] Preferably, the three-dimensional graphene / metal oxide composite spheres have a multi-level pore structure with an average pore diameter of 0.1-50 nm.

[0010] Preferably, the diameter of the three-dimensional graphene / metal oxide composite sphere is 0.5-5 mm.

[0011] Preferably, the metal oxide is selected from WO 3 , CuO, ZnO, Co 3 O4 、MoO 3 and SnO 2 One or more of the following.

[0012] Preferably, the method for preparing the three-dimensional graphene / metal oxide composite spheres comprises the following steps:

[0013] (1) mixing graphene oxide, sodium alginate and water, and then performing ultrasound and heating to obtain a mixed dispersion;

[0014] (2) The mixed dispersion was dropped into a solution containing Ca by a syringe pump. 2+ soaking the graphene oxide / sodium alginate hydrogel in an aqueous solution to obtain graphene oxide / sodium alginate hydrogel, and washing the graphene oxide / sodium alginate hydrogel to obtain graphene oxide spheres;

[0015] (3) mixing the graphene oxide beads, metal salt and water to obtain a mixture;

[0016] (4) subjecting the mixture to a hydrothermal reaction, and then sequentially subjecting the mixture to solid-liquid separation, washing, freeze-drying and sintering.

[0017] Preferably, in step (1), the weight ratio of the graphene oxide, sodium alginate and water is 1-15:0.1-50:1000, preferably 5-10:0.1-40:1000.

[0018] Preferably, in step (1), the ultrasonication time is 10-120 min.

[0019] Preferably, in step (1), the heating conditions include: temperature of 70-95° C. and time of 3-6 h.

[0020] Preferably, in step (2), the flow rate of the syringe pump is 10-200 μL / min.

[0021] Preferably, in step (2), the Ca 2+ Ca in aqueous solution 2+ The concentration is 1-10% by weight.

[0022] Preferably, in step (2), the soaking time is 1-24 hours.

[0023] Preferably, in step (2), the washing process comprises: rinsing the graphene oxide / sodium alginate hydrogel with water and then soaking it in water for 12-48 hours.

[0024] Preferably, in step (3), the metal salt is selected from one or more of tungstates, copper salts, cobalt salts, zinc salts, molybdates and tin salts.

[0025] Preferably, the metal salt is selected from one or more of sodium tungstate, copper sulfate, zinc nitrate, cobalt nitrate, ammonium molybdate and stannous chloride.

[0026] Preferably, in step (3), the weight ratio of the graphene oxide beads, the metal salt and the water is 1:1-20:2000-2600.

[0027] Preferably, in step (4), the hydrothermal reaction is a microwave hydrothermal reaction.

[0028] Preferably, the conditions of the microwave hydrothermal reaction include: temperature of 150-220° C., time of 0.5-6 h, and microwave power of 400-800 W.

[0029] Preferably, in step (4), the freeze-drying conditions include: temperature of 25-60°C and time of 12-48h.

[0030] Preferably, in step (4), the sintering conditions are: temperature of 200-700° C., time of 1-5 h, and inert atmosphere.

[0031] A second aspect of the present invention provides a gas sensor for detecting H in a gas. 2 Application of S concentration.

[0032] A third aspect of the present invention provides a method for detecting H in gas. 2 The method comprises the following steps: applying voltage to a gas sensor, then introducing a gas to be tested so as to contact the gas with the three-dimensional graphene / metal oxide composite sphere, and determining the H 2 The concentration of S;

[0033] The gas sensor is the gas sensor described above.

[0034] Preferably, the voltage is 0.1-15V.

[0035] The present invention adopts a two-step method to prepare three-dimensional graphene / metal oxide composite spheres, and then prepares the spheres into a gas sensor capable of self-heating. The gas sensor is based on the Joule principle and utilizes the three-dimensional structure and synergistic effect of the three-dimensional graphene / metal oxide composite spheres to reduce the operating temperature and sensor power consumption, thereby achieving low-power gas detection, which is beneficial to the miniaturization and portability of the sensor and is very suitable for application in the field of gas monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a schematic diagram of a gas sensor;

[0037] Figure 2is an optical scanning photograph of the three-dimensional graphene / metal oxide composite sphere in Example 1;

[0038] Figure 3 This is a picture of nitrogen adsorption and desorption performance of three-dimensional graphene / metal oxide composite beads in Example 1;

[0039] Figure 4 is a scanning electron microscope image of the three-dimensional graphene / metal oxide composite sphere in Example 1;

[0040] Figure 5 is a graph showing the power of the gas sensor in Example 1 as a function of voltage;

[0041] Figure 6 is a graph showing power versus voltage variation of the gas sensor in Example 2;

[0042] Figure 7 is a graph showing the change in the response value of the gas sensor to 20 ppm hydrogen sulfide as a function of voltage in Example 1;

[0043] Figure 8 is a curve diagram showing the response value of the gas sensor to 20 ppm hydrogen sulfide as a function of voltage in Example 2;

[0044] Fig. 9 is a graph showing the temperature of the gas sensor in Example 1 as a function of voltage;

[0045] Fig.10 is a curve diagram showing the response time of the gas sensor to 20 ppm hydrogen sulfide as a function of voltage in Example 1;

[0046] Fig.11 is a result diagram of the response values ​​of the gas sensor in Example 1 to different gases at a voltage of 2V;

[0047] Fig.12 is a graph showing the change in response value of the gas sensor in Example 1 to 20 ppm hydrogen sulfide at a voltage of 2 V within 30 days;

[0048] Fig.13 is a graph showing the temperature of the gas sensor as a function of voltage in Example 2;

[0049] Fig.14 is a curve diagram of the response value of the gas sensor in Example 2 to different concentrations of hydrogen sulfide at a voltage of 9V;

[0050] Fig.15 1 is a graph showing the response values ​​of the gas sensor to different gases at a voltage of 9 V in Example 2;

[0051] Fig.16 is a curve diagram of the response value of the gas sensor in Example 1 to different concentrations of hydrogen sulfide at a voltage of 2V;

[0052] Fig.17 is a curve diagram of the response value of the gas sensor in Example 1 to different concentrations of hydrogen sulfide at a voltage of 5V;

[0053] Fig.18 It is a curve diagram of the response value of the gas sensor in Example 1 to different concentrations of hydrogen sulfide at a voltage of 0.3V.

[0054] Description of Reference Numerals

[0055] 1. Ceramic packaging; 2. Three-dimensional graphene / metal oxide composite sphere; 11. Groove; 12. Pin. DETAILED DESCRIPTION

[0056] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0057] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0058] On one hand, the present invention provides a gas sensor, which includes a ceramic package 1 and a three-dimensional graphene / metal oxide composite ball 2 suspended in a groove 11 of the ceramic package 1, and the three-dimensional graphene / metal oxide composite ball 2 is connected to a pin 12 of the ceramic package 1 through a wire;

[0059] The three-dimensional graphene / metal oxide composite sphere 2 comprises a graphene sphere and a metal oxide supported on the graphene sphere;

[0060] The specific surface area of ​​the three-dimensional graphene / metal oxide composite sphere 2 is 50-500m 2 / g.

[0061] The gas sensor of the present invention is shown in the schematic diagram Figure 1 As shown, the ceramic package 1 can be a common ceramic package in the art and can be purchased commercially. There are no special requirements for the size and shape of the ceramic package 1, as long as the three-dimensional graphene / metal oxide composite ball 2 can be suspended in the groove 11 of the ceramic package 1.

[0062] In a specific embodiment of the present invention, the method for preparing the gas sensor includes: using a lead wire machine to lead out a wire from the three-dimensional graphene / metal oxide composite ball 2, and then connecting the wire to the pin 12 of the ceramic package 1.

[0063] In a specific embodiment of the present invention, in order to improve conductivity, the conductive wire is a gold wire.

[0064] Preferably, the three-dimensional graphene / metal oxide composite spheres 2 have a multi-level pore structure with an average pore diameter of 0.1-50 nm, for example, 0.1 nm, 1 nm, 5 nm, 20 nm, 30 nm, 40 nm or 50 nm.

[0065] Preferably, the diameter of the three-dimensional graphene / metal oxide composite sphere 2 is 0.5-5 mm.

[0066] In the present invention, in order to make the three-dimensional graphene / metal oxide composite ball 2 have better gas sensing performance, it is also necessary to control the specific surface area of ​​the three-dimensional graphene / metal oxide composite ball 2 within the above range in a preferred embodiment. In a specific embodiment, the specific surface area of ​​the three-dimensional graphene / metal oxide composite ball 2 can be 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g, 350m 2 / g or 500m 2 / g.

[0067] Preferably, the metal oxide is selected from WO 3 , CuO, ZnO, Co 3 O 4 、MoO 3 and SnO 2 One or more of the following.

[0068] The second aspect of the present invention provides a method for preparing the above-mentioned three-dimensional graphene oxide / metal oxide composite sphere 2, the preparation method comprising the following steps:

[0069] (1) mixing graphene oxide, sodium alginate and water, and then performing ultrasound and heating to obtain a mixed dispersion;

[0070] (2) The mixed dispersion was dropped into a solution containing Ca by a syringe pump. 2+ soaking the graphene oxide / sodium alginate hydrogel in an aqueous solution to obtain graphene oxide / sodium alginate hydrogel, and washing the graphene oxide / sodium alginate hydrogel to obtain graphene oxide spheres;

[0071] (3) mixing the graphene oxide beads, metal salt and water to obtain a mixture;

[0072] (4) subjecting the mixture to a hydrothermal reaction, and then sequentially subjecting the mixture to solid-liquid separation, washing, freeze-drying and sintering.

[0073] In the present invention, graphene oxide, as the single-layer material peeled off from graphite oxide, can stably exist in aqueous solution and polar solvent due to the introduction of a large amount of oxygen-containing groups on the surface and the edge. After oxidation treatment, graphite oxide still keeps the layered structure of graphite, but introduces many oxygen functional groups on the graphene monolith of each layer. The introduction of these oxygen functional groups makes the single graphene structure become very complicated. In view of the status of graphene oxide in the field of graphene materials, many scientists attempt to describe the structure of graphene oxide in detail and accurately, so as to be conducive to the further research of graphene materials, although computer simulation, Raman spectroscopy have been utilized, and means such as nuclear magnetic resonance are analyzed to its structure, but due to various reasons (different preparation methods, the difference of experimental conditions and different graphite sources have a certain influence on the structure of graphene oxide), the precise structure of graphene oxide cannot be determined. The generally accepted structural model is that hydroxyl and epoxy groups are randomly distributed on a graphene oxide sheet, while carboxyl and carbonyl groups are introduced at the edges of the sheet. However, relevant theoretical analysis shows that the surface functional groups of graphene oxide are not randomly distributed, but are highly correlated.

[0074] Sodium alginate is a byproduct of extracting iodine and mannitol from brown algae such as kelp or sargassum. Its molecule is composed of β-D-mannuronic acid (β-D-mannuronic, M) and α-L-guluronic acid (α-L-guluronic, G) connected by (1→4) bonds. The aqueous solution of sodium alginate has a high viscosity and is easy to form a gel under mild conditions. When there is Ca 2+ , Sr 2+ In the presence of cations, the Na on the G unit + Ion exchange reaction occurs with divalent cations, and the G units stack to form a cross-linked network structure, thereby forming a hydrogel.

[0075] In the present invention, in order to facilitate the formation of graphene / sodium alginate hydrogel and obtain graphene spheres with better performance, it is necessary to reasonably control the amount of graphene oxide, sodium alginate and water. The addition of sodium alginate can increase the viscosity and strength of the dispersion and prevent the dispersion from dripping from the injection pump to the Ca 2+ When in solution, it deforms due to low strength; however, the dosage of sodium alginate should not be too high. Too much sodium alginate will cause the dispersion to be too viscous and clog the injection pump.

[0076] Therefore, in a preferred case, in step (1), the weight ratio of the graphene oxide, sodium alginate and water is 1-15:0.1-50:1000, and more preferably 5-10:0.1-40:1000.

[0077] In a specific embodiment, in step (1), the weight ratio of the graphene oxide to water can be 5:1000, 6:1000, 7:1000, 8:1000, 9:100 or 10:1000, and the weight ratio of the sodium alginate to water can be 0.1:1000, 1:1000, 5:1000, 10:1000, 15:1000, 20:1000, 25:1000, 30:1000, 35:1000 or 40:1000.

[0078] In the present invention, in step (1), since the viscosity of the whole system increases after the addition of sodium alginate, it is necessary to completely disperse the graphene oxide by ultrasound, and the ultrasound time can be adjusted according to the amount of sodium alginate added. Preferably, in step (1), the ultrasound time is 10-120 minutes, specifically 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes or 120 minutes.

[0079] In the present invention, in step (1), the heating operation can completely dissolve the sodium alginate and prevent agglomeration, and the heating time is related to the amount of sodium alginate added. In a preferred embodiment, the heating conditions include: a temperature of 70-95° C. and a time of 3-6 hours.

[0080] In a specific embodiment, in step (1), the heating temperature can be 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, and the heating time can be 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h.

[0081] Preferably, in step (2), in step (2), the flow rate of the injection pump is 10-200 μL / min, specifically 10 μL / min, 30 μL / min, 50 μL / min, 70 μL / min, 90 μL / min, 110 μL / min, 130 μL / min, 150 μL / min, 180 μL / min or 200 μL / min.

[0082] In the present invention, in step (2), Ca 2+ In aqueous solution, if Ca 2+ If the concentration of Ca is too low, the strength of the gel will be too low. 2+If the concentration is too high, too much will remain in the gel, affecting the structure and performance. Therefore, in a preferred embodiment, preferably, in step (2), the Ca 2+ Ca in aqueous solution 2+ The concentration is 1-10 weight %, specifically 1 weight %, 2 weight %, 3 weight %, 4 weight %, 5 weight %, 6 weight %, 7 weight %, 8 weight %, 9 weight % or 10 weight %.

[0083] In the present invention, the Ca 2+ The aqueous solution can be obtained by mixing various water-soluble calcium salts commonly used in the art with water. 2+ The solution is a calcium chloride aqueous solution.

[0084] In step (2) of the present invention, the Ca-containing 2+ There is no special requirement for the amount of the aqueous solution used, as long as it can completely soak the mixed dispersion dripped by the injection pump.

[0085] In the present invention, in step (2), the soaking time is counted from the completion of the dropwise addition to the end of the soaking. Preferably, in step (2), the soaking time is 1-24 hours, more preferably 6-24 hours. Specifically, the soaking time can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 2 hours or 24 hours.

[0086] In the present invention, in order to fully remove calcium ions in the hydrogel, the product can be washed by rinsing and soaking. Therefore, in the preferred case of step (2), the washing process includes: rinsing the graphene oxide / sodium alginate hydrogel with water, and then soaking it in water for 12-48 hours, and the specific soaking time can be 12 hours, 16 hours, 18 hours, 20 hours, 24 hours, 30 hours, 32 hours, 36 hours, 40 hours or 48 hours.

[0087] Preferably, in step (2), the number of rinses during the washing process is 1-5 times.

[0088] In step (3) of the present invention, the metal salt is selected from one or more of tungstates, copper salts, cobalt salts, zinc salts, molybdates and tin salts, and is more preferably a soluble salt.

[0089] In a preferred embodiment of the present invention, the tungstate is used to provide the tungsten element and may be a soluble tungstate commonly used in the art, for example, one or more of potassium tungstate, sodium tungstate and ammonium tungstate.

[0090] In a preferred embodiment of the present invention, the copper salt is used to provide the copper element and may be a soluble copper salt commonly used in the art, for example, one or more of copper chloride, copper sulfate and copper nitrate.

[0091] In a preferred embodiment of the present invention, the cobalt salt is used to provide the cobalt element and may be a soluble cobalt salt commonly used in the art, for example, one or more of cobalt chloride, cobalt carbonate, cobalt sulfate and cobalt nitrate.

[0092] In a preferred embodiment of the present invention, the zinc salt is used to provide the zinc element and may be a soluble zinc salt commonly used in the art, for example, one or more of zinc chloride, zinc sulfate and zinc nitrate.

[0093] In a preferred embodiment of the present invention, the molybdate is used to provide the molybdenum element and may be a soluble molybdate commonly used in the art, for example, one or more of potassium molybdate, ammonium molybdate and sodium molybdate.

[0094] In a preferred embodiment of the present invention, the tin salt is used to provide the tin element and can be a soluble tin salt commonly used in the art.

[0095] Preferably, in step (3), the metal salt is selected from one or more of sodium tungstate, copper sulfate, zinc nitrate, cobalt nitrate, ammonium molybdate and stannous chloride.

[0096] Preferably, in step (3), the weight ratio of the graphene oxide beads, the metal salt and the water is 1:1-20:2000-2600.

[0097] In a specific implementation of step (3), the weight ratio of the graphene oxide spheres to the metal salt can be 1:1, 1:5, 1:10, 1:15 or 1:20, and the weight ratio of the graphene oxide spheres to water is 1:2000, 1:2100, 1:2200, 1:2300, 1:2400, 1:2500 or 1:2600.

[0098] In step (3) of the present invention, due to the different metal salts used, a certain amount of acid or base needs to be added to adjust the pH value to a suitable range to form a stably dispersed hydrosol, thereby ensuring uniform growth into nano-metal oxides during the heating process.

[0099] Therefore, in a specific embodiment of the present invention, when the metal salt is sodium tungstate, the specific process of step (3) includes: after mixing the graphene oxide beads, the metal salt and water, then adding a hydrochloric acid solution with a concentration of 2 mol / L dropwise under stirring, adjusting the pH value to 1.5-2.5, and then obtaining a mixture, wherein the dripping time of the hydrochloric acid solution is controlled to be 10-30 min; wherein, there is no special requirement for the dripping speed of the hydrochloric acid solution, and the addition can be completed within the specified time.

[0100] In a specific embodiment of the present invention, when the metal salt is copper sulfate, the specific process of step (3) includes: mixing the graphene oxide beads, the metal salt and water, and then adding a sodium hydroxide solution with a concentration of 2 mol / L dropwise under stirring, adjusting the pH value to 9.5-10.5, and then obtaining a mixture, wherein the dropping time of the sodium hydroxide solution is controlled to be 10-30 min; wherein there is no special requirement for the dropping speed of the sodium hydroxide solution, and the dropping can be completed within a limited time.

[0101] In a specific embodiment of the present invention, when the metal salt is zinc nitrate, the specific process of step (3) comprises: mixing the graphene oxide beads, the metal salt and water, and then adding a sodium hydroxide solution with a concentration of 2 mol / L dropwise under stirring, adjusting the pH value to 9.5-10.5, and then obtaining a mixture, wherein the dropping time of the sodium hydroxide solution is controlled to be 10-30 min; wherein there is no special requirement for the dropping speed of the sodium hydroxide solution, and the dropping can be completed within a limited time.

[0102] In a specific embodiment of the present invention, when the metal salt is cobalt nitrate, the specific process of step (3) comprises: mixing the graphene oxide beads, the metal salt and water, and then adding dropwise a 2 mol / L sodium hydroxide solution under stirring to adjust the pH value to 9.5-10.5, and then obtaining a mixture, wherein the dropping time of the sodium hydroxide solution is controlled to be 10-30 min; wherein there is no special requirement for the dropping speed of the sodium hydroxide solution, and the dropping can be completed within a limited time.

[0103] In a specific embodiment of the present invention, when the metal salt is ammonium molybdate, the specific process of step (3) includes: mixing the graphene oxide beads, the metal salt and water, and then adding a nitric acid solution with a concentration of 2 mol / L dropwise under stirring, adjusting the pH value to 1.5-2.5, and then obtaining a mixture, wherein the dropping time of the nitric acid solution is controlled to be 10-30 min; wherein there is no special requirement for the dropping speed of the nitric acid solution, and the dropping can be completed within a limited time.

[0104] In a specific embodiment of the present invention, when the metal salt is stannous chloride, stannous chloride can hydrolyze by itself and form a stably dispersed hydrosol, so there is no need to add acid or alkali. Therefore, when the metal salt is stannous chloride, the specific process of step (3) includes: mixing the graphene oxide beads, the metal salt and water, and then stirring for 10-30 minutes to obtain a mixture.

[0105] In a specific embodiment of the present invention, in step (3), when sodium hydroxide solution, hydrochloric acid solution or nitric acid solution is added, the amount of water used is calculated based on the total amount of water added and the water contained in the added solution. When the water content in the added sodium hydroxide solution, hydrochloric acid solution or nitric acid solution meets the required ratio of the amounts of graphene oxide beads, metal salt and water, no additional water may be added.

[0106] In a preferred case, in step (4), the hydrothermal reaction is a microwave hydrothermal reaction. The use of microwave hydrothermal method is conducive to obtaining nanomaterials with more uniform size distribution, improving the stability of the material, and greatly shortening the reaction time.

[0107] Preferably, the conditions of the microwave hydrothermal reaction include: temperature of 150-220° C., time of 0.5-6 h, and microwave power of 400-800 W.

[0108] In a specific embodiment of step (4), the temperature of the microwave hydrothermal reaction can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C, the time of the microwave hydrothermal reaction can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, and the microwave power can be 400W, 500W, 600W, 700W or 800W.

[0109] In a preferred embodiment, in step (4), when washing the solid phase obtained by solid-liquid separation, anhydrous ethanol and deionized water are used in sequence.

[0110] More preferably, the number of washings using anhydrous ethanol is 2-5 times, and the number of washings using deionized water is 2-5 times.

[0111] In the present invention, freeze drying is used in step (4) to prevent the pore structure of the gel from collapsing, thereby retaining the three-dimensional structure of the spheres to the greatest extent.

[0112] Therefore, preferably, in step (4), the freeze-drying conditions include: temperature of 25-60°C and time of 12-48h.

[0113] In a specific embodiment of step (4), the freeze-drying temperature can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, and the freeze-drying time can be 12h, 18h, 24h, 30h, 36h, 42h or 48h.

[0114] In step (4) of the present invention, the sintering operation can remove sodium alginate on the one hand, and reduce graphene oxide on the other hand, thereby improving its electrical conductivity and mechanical properties, while improving the crystal structure of the metal oxide.

[0115] Therefore, preferably, in step (4), the sintering conditions are: temperature of 200-700°C, time of 1-5h, and inert atmosphere. Specifically, the sintering temperature can be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C, and the sintering time can be 1h, 2h, 3h, 4h or 5h.

[0116] Further preferably, in step (4), the inert atmosphere can be provided by one or more gases selected from the group consisting of nitrogen, helium, neon, argon, krypton and xenon.

[0117] A second aspect of the present invention provides a gas sensor for detecting H in a gas. 2 Application of S concentration.

[0118] A third aspect of the present invention provides a method for detecting H in gas. 2 The method comprises the following steps: applying voltage to the gas sensor, then introducing the gas to be tested to contact the three-dimensional graphene / metal oxide composite ball 2, and determining the H concentration by measuring the response value after contact. 2 The concentration of S;

[0119] The gas sensor is the gas sensor described above.

[0120] In the detection gas described in the present invention, H 2 In the method for measuring the concentration of S, a voltage is applied to the gas sensor so that the three-dimensional graphene / metal oxide composite ball 2 is charged. According to the Joule heat principle (Joule heat: heat generated when current passes through a conductor), the charged three-dimensional graphene / metal oxide composite ball 2 is self-heated. The resistance change of the gas sensor is measured before and after the charged three-dimensional graphene / metal oxide composite ball 2 contacts the gas to be measured, and then the response value S (Sensitivity) of the gas sensor to the gas to be measured is calculated to be (R 0 -R x ) / R 0 , where R 0is the resistance value of the gas sensor in the air, R x It is the resistance value of the gas sensor after the gas to be tested is introduced.

[0121] In the present invention, the voltage is 0.1-15V.

[0122] It should be noted that since the preparation process of the three-dimensional graphene / metal oxide composite spheres 2 in the gas sensor may be different, the resistance of the obtained three-dimensional graphene / metal oxide composite spheres 2 will also be different, which will cause the range of voltage that can be applied to the gas sensor (i.e., the tolerable voltage) to be different when the three-dimensional graphene / metal oxide composite spheres 2 are different.

[0123] In a specific embodiment, an external standard method can be used to detect H in the gas. 2 S concentration, the specific process includes: mixing different proportions of H 2 S is mixed with air to prepare a gradient concentration of H 2 S standard gas, apply voltage to the gas sensor through the power source, and then pass the above H 2 After the S standard gas comes into contact with the charged three-dimensional graphene / metal oxide composite ball 2, the resistance value of the gas sensor is measured, and then the response value of the gas sensor is calculated; 2 The S concentration is the horizontal axis, and the response value of the gas sensor is the vertical axis. The H 2 S concentration-response value standard curve, then at the same voltage, the gas to be tested is tested using the same method to obtain the response value of the gas sensor under the gas to be tested, and the obtained response value of the gas sensor is brought into the H 2 The H content in the gas to be tested can be obtained from the S concentration-response value standard curve. 2 The concentration of S; where H 2 The gas sensors used for the S standard gas and the gas to be tested are from the same batch of gas sensors.

[0124] The present invention is used to detect H in gas 2 The S concentration method can be used to detect low concentration H 2 S, vs. H 2 The gas under test with S concentration of 5-50ppm can still show excellent detection performance.

[0125] The gas sensor of the present invention utilizes the Joule heat principle for self-heating. By adjusting the resistance and the applied measurement voltage, heating can be achieved using the current provided by the measurement circuit. Moreover, since the heating is directly generated by the three-dimensional graphene / metal oxide composite spheres themselves, no heat conduction is required in the middle, which can greatly reduce heat dissipation. Moreover, after removing the external heating circuit, energy consumption can be further reduced.

[0126] Since the ceramic tubes and MEMS chips used in traditional gas sensors are equipped with external heating elements, the present invention utilizes the Joule heat of the material for self-heating, so these external heating elements can be removed, thereby simplifying their design, facilitating processing and miniaturization of circuits.

[0127] Compared with the prior art, the beneficial effects of the present invention are mainly:

[0128] 1. Prepare gas sensors with three-dimensional graphene / metal oxide composite spheres without coating on ceramic tubes or MEMS chips, simplifying the process and reducing the size of the device;

[0129] 2. Improve the performance of the sensor through self-heating, while removing external heating elements, reducing heat dissipation, reducing power consumption, and achieving low-power rapid detection.

[0130] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0131] In the following examples, the ceramic package used was purchased from Kyocera, with the product number CLCC28.

[0132] The room temperature below refers to 25℃.

[0133] Example 1

[0134] (1) Dispersing 50 mg of graphene oxide into 10 ml (10 g) of deionized water, adding 0.1 g of sodium alginate, and stirring evenly, that is, the weight ratio of graphene oxide, sodium alginate and deionized water is 5:10:1000; then ultrasonicating for 30 min to completely peel off the graphene oxide sheets and evenly disperse them in water, and then heating at 70 ° C for 4 h to obtain a mixed dispersion;

[0135] (2) Add the mixed dispersion into a microinjection pump and control the flow rate of the injection pump to 30 μL / min so that the mixed dispersion drops evenly onto the calcium chloride aqueous solution (Ca 2+ The graphene oxide / sodium alginate hydrogel was rinsed with deionized water for 3 times, and then immersed in deionized water for 24 hours to obtain graphene oxide spheres;

[0136] (3) 0.1 g of graphene oxide beads were added to a 500 mL beaker, and then 190 mL (190 g) of deionized water was added, followed by 1.06 g of sodium tungstate, and a 2 mol / L hydrochloric acid solution was added dropwise at room temperature and under stirring to adjust the pH value to 2, wherein the addition time of the hydrochloric acid solution was controlled to be 30 min, to obtain a mixture, wherein the weight ratio of the graphene oxide beads, sodium tungstate and water was 1:10.6:2400 (the amount of water at this time was the amount of deionized water plus the water content in the hydrochloric acid solution), and the mixture was a uniform suspension;

[0137] (4) The mixture was transferred to a hydrothermal reactor and then placed in a microwave synthesizer for microwave-assisted hydrothermal treatment at 180°C (microwave power 800 W) for 0.5 h. After naturally cooling to room temperature, the solid obtained by solid-liquid separation was washed three times with anhydrous ethanol and deionized water, respectively, and then freeze-dried at 25°C for 24 h. Then, it was sintered at 500°C for 2 h under nitrogen protection to obtain three-dimensional graphene / metal oxide composite spheres (three-dimensional graphene / WO 3 The morphology of the obtained three-dimensional graphene / metal oxide composite spheres was detected by scanning electron microscopy and nitrogen adsorption and desorption method (BET method). Figure 2 as well as Figure 4 As shown, according to Figure 2 Yes, the three-dimensional graphene / metal oxide composite spheres are uniformly spherical with a diameter of 1.78 mm. Figure 4 It can be seen that WO was successfully loaded on the surface of the graphene sphere by the in-situ loading method. 3 Nanosheets and WO 3 The nanosheets are evenly distributed on the surface of the graphene spheres. The BET test results are as follows: Figure 3 As shown, it can be seen that the specific surface area is 206m 2 / g, with a very high specific surface area and multi-level pores ranging from 2 nanometers to 100 nanometers, with an average pore diameter of 10.38nm;

[0138] (5) Using a lead wire machine, lead the wire (gold wire) from the three-dimensional graphene / metal oxide composite ball obtained in step (4) and connect it to the pin of the ceramic package to obtain a gas sensor A1, as shown in the schematic diagram. Figure 1 As shown, the gas sensor includes a ceramic package 1 and a three-dimensional graphene / metal oxide composite ball suspended in a groove 11 of the ceramic package 1, and the three-dimensional graphene / metal oxide composite ball is connected to a pin 12 of the ceramic package 1 through a wire.

[0139] Example 2

[0140] The method of Example 1 is used, except that the operation of step (3) is as follows: 0.1 g of graphene oxide beads is added to a 500 mL beaker, and then 220 mL (220 g) of deionized water is added, followed by 0.55 g of copper sulfate, and a 2 mol / L sodium hydroxide solution is added dropwise at room temperature and under stirring, the pH value is adjusted to 10, and the dropping time of the sodium hydroxide solution is controlled to be 30 min, and then a mixture is obtained, wherein the weight ratio of the graphene oxide beads, copper sulfate and water is 1:5.5:2400 (the amount of water at this time is the amount of deionized water plus the water content in the sodium hydroxide solution); finally, three-dimensional graphene / metal oxide composite beads are obtained (the three-dimensional graphene / CuO composite beads are uniformly spherical, with a diameter of 1.2 mm and a specific surface area of ​​190 m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers, with an average pore diameter of 11.71nm) and gas sensor A2.

[0141] Example 3

[0142] The method of Example 1 is used, except that the operation of step (3) is as follows: 0.1 g of graphene oxide beads is added to a 500 mL beaker, and then 220 mL (220 g) of deionized water is added, followed by 1.428 g of zinc nitrate, and a 2 mol / L sodium hydroxide solution is added dropwise at room temperature and under stirring, the pH value is adjusted to 10, and the dropping time of the sodium hydroxide solution is controlled to be 30 min, and then a mixture is obtained, wherein the weight ratio of the graphene oxide beads, zinc nitrate and water is 1:14.28:2400 (the amount of water at this time is the amount of deionized water plus the water content in the sodium hydroxide solution); finally, three-dimensional graphene / metal oxide composite beads are obtained (the three-dimensional graphene / ZnO composite beads are uniformly spherical, with a diameter of 1.3 mm and a specific surface area of ​​193 m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers with an average pore diameter of 10.9nm) and gas sensor A3.

[0143] Example 4

[0144] The method of Example 1 is used, except that the operation of step (3) is as follows: 0.1 g of graphene oxide beads is added to a 500 mL beaker, and then 220 mL (220 g) of deionized water is added, followed by 1.164 g of cobalt nitrate, and a 2 mol / L sodium hydroxide solution is added dropwise at room temperature and under stirring, the pH value is adjusted to 10, and the dropping time of the sodium hydroxide solution is controlled to be 30 min, and then a mixture is obtained, wherein the weight ratio of the graphene oxide beads, cobalt nitrate and water is 1:11.64:2400 (the amount of water at this time is the amount of deionized water plus the water content in the sodium hydroxide solution); finally, three-dimensional graphene / metal oxide composite beads (three-dimensional graphene / Co) are obtained. 3 O 4 The composite beads were detected by scanning electron microscopy and nitrogen adsorption and desorption method (BET method). The obtained three-dimensional graphene / metal oxide composite beads were uniformly spherical, with a diameter of 1.7 mm and a specific surface area of ​​188 m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers, with an average pore diameter of 14.4nm) and gas sensor A4.

[0145] Example 5

[0146] The method of Example 1 is used, except that the operation of step (3) is as follows: 0.1 g of graphene oxide beads are added to a 500 mL beaker, and then 220 mL (220 g) of deionized water is added, followed by 1.76 g of ammonium molybdate, and a nitric acid solution with a concentration of 2 mol / L is added dropwise at room temperature and under stirring, the pH value is adjusted to 2, and the dropping time of the nitric acid solution is controlled to be 30 min, and then a mixture is obtained, wherein the weight ratio of the graphene oxide beads, ammonium molybdate and water is 1:17.6:2400 (the amount of water at this time is the amount of deionized water plus the water content in the nitric acid solution); finally, three-dimensional graphene / metal oxide composite beads (three-dimensional graphene / MoO 3 The composite beads were detected by scanning electron microscopy and nitrogen adsorption and desorption method (BET method). The obtained three-dimensional graphene / metal oxide composite beads were uniformly spherical, with a diameter of 1.5 mm and a specific surface area of ​​202 m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers, with an average pore diameter of 10.57nm) and gas sensor A5.

[0147] Example 6

[0148] The method of Example 1 is used, except that the operation of step (3) is as follows: 0.1 g of graphene oxide beads are added to a 500 mL beaker, and then 240 mL (240 g) of deionized water is added, followed by 1.2 g of stannous chloride, that is, the weight ratio of the graphene oxide beads, stannous chloride and deionized water is 1:12:2400, and the mixture is stirred at room temperature for 30 min to obtain a mixture; finally, three-dimensional graphene / metal oxide composite beads (three-dimensional graphene / SnO 2 The composite beads were detected by scanning electron microscopy and nitrogen adsorption and desorption method (BET method). The obtained three-dimensional graphene / metal oxide composite beads were uniformly spherical, with a diameter of 0.9 mm and a specific surface area of ​​189 m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers, with an average pore diameter of 11.87nm) and gas sensor A6.

[0149] Example 7

[0150] The method of Example 1 is used, except that the operation of step (1) is as follows:

[0151] 50 mg of graphene oxide was dispersed in 5 mL of deionized water, and 0.1 g of sodium alginate was added and stirred evenly, that is, the weight ratio of graphene oxide, sodium alginate and water was 10:20:1000; then ultrasonication was performed for 100 min to completely peel off the graphene oxide sheets and evenly disperse them in water, and then heated at 70 ° C for 4 h to obtain a mixed dispersion; finally, three-dimensional graphene / metal oxide composite beads (three-dimensional graphene / WO 3 The composite beads were detected by scanning electron microscopy and nitrogen adsorption and desorption method (BET method). The obtained three-dimensional graphene / metal oxide composite beads were uniformly spherical, with a diameter of 1.7 mm and a specific surface area of ​​197 m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers with an average pore diameter of 10.52nm) and gas sensor A7.

[0152] Example 8

[0153] The method of Example 1 is used, except that the operation of step (2) is as follows:

[0154] Add the mixed dispersion into the microinjection pump and control the flow rate of the injection pump to 100uL / min so that the mixed dispersion drops evenly onto the calcium chloride aqueous solution (Ca 2+The graphene oxide / sodium alginate hydrogel was rinsed with deionized water for 3 times, and then immersed in deionized water for 24 hours to obtain graphene oxide spheres; finally, three-dimensional graphene / metal oxide composite spheres (three-dimensional graphene / WO 3 The composite beads were detected by scanning electron microscopy and nitrogen adsorption and desorption method (BET method). The obtained three-dimensional graphene / metal oxide composite beads were uniformly spherical, with a diameter of 1.6 mm and a specific surface area of ​​191 m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers, with an average pore diameter of 11.55nm) and gas sensor A8.

[0155] Example 9

[0156] The method of Example 1 is used, except that the operation of step (4) is as follows:

[0157] The mixture was transferred to a hydrothermal reactor and then placed in a microwave synthesizer for microwave-assisted hydrothermal treatment at 200°C (microwave power 800W) for 3 hours. After naturally cooling to room temperature, the solid obtained by solid-liquid separation was washed three times with anhydrous ethanol and deionized water, respectively, and then freeze-dried at 50°C for 24 hours, and then sintered at 500°C for 4 hours under nitrogen protection to obtain three-dimensional graphene / metal oxide composite spheres (three-dimensional graphene / WO 3 The composite beads were detected by scanning electron microscopy and nitrogen adsorption and desorption method (BET method). The obtained three-dimensional graphene / metal oxide composite beads were uniformly spherical, with a diameter of 1.9 mm and a specific surface area of ​​192 m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers with an average pore diameter of 11.16nm) and gas sensor A9.

[0158] Example 10

[0159] The method of Example 1 was followed, except that in step (4), the sintering temperature was 200° C. to obtain three-dimensional graphene / metal oxide composite beads (three-dimensional graphene / WO 3 The composite beads were detected by scanning electron microscopy and nitrogen adsorption and desorption method (BET method). The obtained three-dimensional graphene / metal oxide composite beads were uniformly spherical, with a diameter of 1.9 mm and a specific surface area of ​​196 m 2 / g, has a very high specific surface area, and has multi-level pores ranging from 2 nanometers to 100 nanometers with an average pore diameter of 10.73nm) and gas sensor A10.

[0160] Comparative Example 1

[0161] The three-dimensional graphene / metal oxide composite beads obtained in Example 1 were ground into powder and coated on a ceramic tube to obtain a gas sensor D1.

[0162] Comparative Example 2

[0163] The method of Example 1 is followed, except that the three-dimensional graphene / metal oxide composite beads are replaced by the graphene oxide beads obtained in step (2), thereby obtaining a gas sensor D2.

[0164] Comparative Example 3

[0165] The method of Example 1 is used, except that the three-dimensional graphene / WO 3 The specific surface area of ​​the composite ball is 32m 2 / g, and obtain gas sensor D3;

[0166] The specific surface area of ​​3D graphene / WO 3 The composite pellets are prepared according to the following method:

[0167] (1) Dispersing 50 mg of graphene oxide into 10 ml (10 g) of deionized water, adding 0.1 g of sodium alginate, and stirring evenly, that is, the weight ratio of graphene oxide, sodium alginate and deionized water is 5:10:1000; then ultrasonicating for 30 min to completely peel off the graphene oxide sheets and evenly disperse them in water, and then heating at 70 ° C for 4 h to obtain a mixed dispersion;

[0168] (2) Add the mixed dispersion into a microinjection pump and control the flow rate of the injection pump to 30 μL / min so that the mixed dispersion drops evenly onto the calcium chloride aqueous solution (Ca 2+ The graphene oxide / sodium alginate hydrogel was rinsed with deionized water for 3 times, and then immersed in deionized water for 24 hours to obtain graphene oxide spheres;

[0169] (3) Add 0.1 g of graphene oxide beads to a 500 mL beaker, then add 240 mL of deionized water, and then add 0.5 g of WO 3 , stirring at room temperature for 30 min, and then obtaining a mixture;

[0170] (4) The mixture was transferred to a hydrothermal reactor and then placed in a microwave synthesizer for microwave-assisted hydrothermal treatment at 180°C (microwave power 800 W) for 0.5 h. After naturally cooling to room temperature, the solid obtained by solid-liquid separation was washed three times with anhydrous ethanol and deionized water, respectively, and then freeze-dried at 25°C for 24 h. Then, it was sintered at 500°C for 2 h under nitrogen protection to obtain three-dimensional graphene / metal oxide composite spheres (three-dimensional graphene / WO 3 The obtained three-dimensional graphene / metal oxide composite spheres were uniformly spherical with a diameter of 6.2 mm and a specific surface area of ​​32 m 2 / g, and the average pore diameter is 63.12nm.

[0171] Test Example 1

[0172] The power changes of A1-A10 and D1-D3 when different voltages are applied and the maximum response values ​​to hydrogen sulfide with a concentration of 20ppm are tested respectively. The test method and test results are as follows:

[0173] 1.1. Electrical performance testing:

[0174] A power meter (Keithley 2601B) was used to apply a voltage of 0-25V to A1-A10 and D1-D3 (wherein the applied voltage interval was 0.1V at 0-1V, 0.5V at 1-10V, and 1V at 10-16V), and an infrared thermometer was used to measure the temperature of the three-dimensional graphene / metal oxide composite spheres in each gas sensor at different voltages, and the minimum applied voltage V of A1-A10 and D1-D3 was detected. min and the maximum applied voltage V max , then V min ~V max is the applicable voltage of the gas sensor, i.e., the withstand voltage. The applicable voltages of A1-A10 and D1-D3 are shown in Table 1, where V min Refers to the voltage applied when the temperature of the three-dimensional graphene / metal oxide composite ball exceeds 25°C for the first time, V max It refers to the maximum voltage that the gas sensor can withstand. When this voltage is exceeded, the temperature of the three-dimensional graphene / metal oxide composite ball is too high, causing the gas sensor to burn out and become unusable.

[0175] Taking A1 as an example, when a voltage less than 0.3V is applied to A1, the temperature of the three-dimensional graphene / metal oxide composite spheres in A1 is ≤25°C. When a voltage of 0.3V is applied to A1, the temperature of the three-dimensional graphene / metal oxide composite spheres is >25°C, that is, the V minis 0.3V; when 5V is applied to A1, A1 is not burned and can be used normally, but when 5.5V is applied to A1, A1 is burned and cannot be used. Therefore, V max is 5V.

[0176] 1.2. Power detection:

[0177] Use the power supply to apply V to A1 min ~V max (0.3~5V) voltage, measure the resistance of the gas sensor under different voltages, and use P=U2 / R to calculate the power of the gas sensor. The power change is as follows Figure 5 As shown;

[0178] Depend on Figure 5 Yes, the power of the gas sensor A1 varies from 0.23 to 29.4 mW when a voltage between 0.3 and 5 V is applied;

[0179] Use the power supply to apply V to A2 min ~V max (0.1~9V), measure the resistance of the gas sensor under different voltages, and use P=U2 / R to calculate the power of the gas sensor. The power change is as follows Figure 6 As shown;

[0180] Depend on Figure 6 Yes, the power of the gas sensor A2 varies from 0.46 to 125.78 mW when a voltage between 0.1 and 9 V is applied;

[0181] The same method is used to detect the power variation range of A3-A10 and D1-D3. The results are shown in Table 1.

[0182] 1.3. Maximum response value to hydrogen sulfide with a concentration of 20ppm:

[0183] Use the power supply to apply V to A1 min ~V max The voltage of (0.3~5V) is set, and a mixture of hydrogen sulfide and air (hydrogen sulfide concentration is 20ppm) is introduced. The response value S of the gas sensor under different voltages is measured, and the maximum response value is obtained. The results are as follows Figure 7 As shown;

[0184] according to Figure 7 Yes, the sensing performance of A1 gradually increases with the increase of voltage. When the voltage is 0.3V, its sensitivity to H 2 The response value of S is smaller. When the voltage reaches 5V, the response value can reach 16%; the maximum response value is 16%.

[0185] Use the power supply to apply V to A2min ~V max The voltage of (0.1~9V) is set, and a mixture of hydrogen sulfide and air (hydrogen sulfide concentration is 20ppm) is introduced. The response value S of the gas sensor under different voltages is measured, and the maximum response value is obtained. The results are as follows Figure 8 As shown,

[0186] according to Figure 8 Yes, the sensing performance of A2 gradually increases with the increase of voltage. When the voltage reaches 9V, the response value can reach more than 25%; the maximum response value is 26.1%.

[0187] The same method is used to detect the response value S of the gas sensors A2-A10 and D1-D3 at different voltages, and the maximum response value is obtained. The results are shown in Table 1.

[0188] Table 1

[0189]

[0190] According to the above results, the gas sensor obtained by the present invention has a lower power, which is much lower than 500mW of the existing sensor, indicating that the gas sensor obtained by the present invention has a lower energy consumption and has a better response effect; in Comparative Example 1, due to the three-dimensional graphene / WO 3 The balls are ground into powder, and their three-dimensional structure and conductive path are destroyed, so the response performance is reduced; in Comparative Example 2, due to the absence of metal oxide, the graphene oxide balls lack active sites for hydrogen sulfide and therefore have no response to hydrogen sulfide; the WO in Comparative Example 3 3 It is compounded onto graphene by physical mixing, which is different from the WO grown in situ by the precursor in the embodiment. 3 Compared with the physically mixed WO 3 It is easier to agglomerate, which causes the specific surface area of ​​the material to drop sharply, thereby reducing the exposed active sites. At the same time, there is a lack of chemical connection with graphene, and the conductive pathway is blocked, resulting in a decrease in response performance.

[0191] Test Example 2

[0192] The self-heating performance, response time to hydrogen sulfide gas, selectivity and stability of A1 were tested respectively. The specific test methods and results are as follows:

[0193] 2.1. Self-heating performance:

[0194] A power source was used to apply a voltage of 1.5-5 V to the gas sensor A1 obtained in Example 1, and an infrared thermometer was used to measure the temperature of the three-dimensional graphene / metal oxide composite ball obtained in Example 1 at different voltages. Fig. 9As shown in Figure 2, the temperature of the three-dimensional graphene / metal oxide composite sphere gradually increases with the increase of voltage, and has a good linear relationship (y = 12.628x + 76.593, R 2 =0.9809, where x represents voltage and y represents temperature), indicating that the three-dimensional graphene / metal oxide composite spheres in A1 have good self-heating properties.

[0195] 2.2. Response time to hydrogen sulfide gas:

[0196] Use the power supply meter to apply a voltage of 0.3-4V to A1 respectively, and pass a mixture of hydrogen sulfide and air (hydrogen sulfide concentration is 20ppm), and measure the response time of the gas sensor under different voltages. The response time of the gas sensor is the time when the resistance change of the gas sensor is 90% of the total change after the mixed gas is passed. The results are as follows Fig.10 shown.

[0197] according to Fig.10 Yes, as the voltage increases, the response time first decreases and then increases. When the voltage is 2V, the response time is the shortest, which is 42s.

[0198] 2.2. Selectivity:

[0199] A voltage of 2V was applied to A1 using a power supply meter, and a mixture of hydrogen sulfide and air (hydrogen sulfide concentration was 20ppm), a mixture of hydrogen and air (hydrogen concentration was 1000ppm), a mixture of carbon monoxide and air (carbon monoxide concentration was 1000ppm), a mixture of methane and air (methane concentration was 1000ppm), and a mixture of ethylene and air (ethylene concentration was 1000ppm) were introduced respectively, and the three-dimensional graphene / metal oxide composite beads were contacted with the above-mentioned mixed gases respectively, and the corresponding response values ​​S were measured. The results are as follows: Fig.11 As shown, the response values ​​are S 硫化氢 =1.6%, S 氢气 =0.04%, S 一氧化碳 =0.06%, S 甲烷 =0.01%, S 乙烯 =0.03%, it can be seen that the gas sensor of the present invention has a significant effect on H 2 ,CO,CH 4 and C 2 H 4 The response value of H 2 The response value of S is relatively high, indicating that the gas sensor of the present invention has a high sensitivity to H 2 S has good selectivity.

[0200] 2.3, Stability:

[0201] Use the power supply to apply 2V voltage to A1, and pass a mixture of hydrogen sulfide and air (hydrogen sulfide concentration is 20ppm), and test its response value S to 20ppm hydrogen sulfide. The first measurement is recorded as the first day, the second measurement is on the fifth day, and then every five days until the 30th day. The results are as follows: Fig.12 As shown, according to Fig.12 After 30 days of testing, the gas sensor of the present invention was found to have a response value change of less than 5% to 20 ppm hydrogen sulfide, indicating that the gas sensor obtained by the present invention has good stability.

[0202] Test Example 3

[0203] The self-heating performance, response performance to different concentrations of hydrogen sulfide and selectivity of A2 were tested respectively. The specific test methods and results are as follows:

[0204] 3.1. Self-heating performance:

[0205] A power source was used to apply a voltage of 0.1-9 V to the gas sensor A2 obtained in Example 2, and an infrared thermometer was used to measure the temperature of the three-dimensional graphene / metal oxide composite ball obtained in Example 2 at different voltages. Fig.13 As shown, the temperature of the three-dimensional graphene / metal oxide composite spheres gradually increases with the increase of voltage. At 9V, the temperature can reach 91°C, indicating that the three-dimensional graphene / metal oxide composite spheres in A2 have good self-heating properties.

[0206] 3.2. Response performance to different concentrations of hydrogen sulfide:

[0207] A power supply meter was used to apply a 9V voltage to A2, and a mixture of hydrogen sulfide and air (the concentrations of hydrogen sulfide were 1ppm, 5ppm, 10ppm, 20ppm, 30ppm, 40ppm and 50ppm) was introduced to measure the hydrogen sulfide concentration of 1-50ppm. 2 S response value S, the result is Fig.14 As shown;

[0208] according to Fig.14 Yes, A2 is resistant to 5-50ppm H 2 Below 20 ppm, the response value and concentration change are relatively linear; above 20 ppm, the response value changes less with the concentration and enters a plateau period. Therefore, the gas sensor obtained by the present invention is suitable for measuring low concentrations of H 2 S.

[0209] 3.3. Selectivity:

[0210] A power meter was used to apply a 9V voltage to A2, and its reaction to the mixture of hydrogen sulfide and air (H2 S concentration is 20ppm), a mixture of hydrogen and air (H 2 concentration is 1000ppm), a mixture of carbon monoxide and air (CO concentration is 1000ppm), a mixture of methane and air (CH 4 concentration of 1000ppm) and a mixture of ethylene and air (C 2 H 4 The response value S of the concentration is 1000ppm, and the result is as follows Fig.15 As shown, S 硫化氢 =26.1%, S 氢气 =4.1%, S 一氧化碳 =6.2%, S 甲烷 =1.3%, S 乙烯 =1.6%, indicating that the gas sensor of the present invention has a high sensitivity to H 2 ,CO,CH 4 and C 2 H 4 The response value of H 2 The response value of S is relatively high, indicating that the gas sensor obtained by the present invention has a high sensitivity to H 2 S has good selectivity.

[0211] Application Example 1

[0212] Different ratios of H 2 S was mixed with air to prepare H 2 S standard gas, a voltage of 2V was applied to the gas sensor A1 obtained in Example 1 using the power supply original meter, and then the above concentrations of H 2 After the S standard gas comes into contact with the charged three-dimensional graphene / metal oxide composite ball, the resistance value of the gas sensor A1 is measured, and then the H concentrations of different concentrations are calculated. 2 The response value of gas sensor A1 under S standard gas; 2 H in S standard gas 2 The S concentration x is the horizontal axis, and the response value y of the gas sensor A1 is the vertical axis. 2 S concentration-response value standard curve, such as Fig.16 As shown, the fitted relationship is y = 0.00004x 3 -0.0048x 2 +0.1835x-0.5346, R 2 =0.9959.

[0213] Application Example 2

[0214] Different ratios of H2 S was mixed with air to prepare H 2 S standard gas, a voltage of 5 V was applied to the gas sensor A1 obtained in Example 1 using the power supply, and then the above concentrations of H 2 After the S standard gas comes into contact with the charged three-dimensional graphene / metal oxide composite ball, the resistance value of the gas sensor A1 is measured, and then the H concentrations of different concentrations are calculated. 2 The response value of gas sensor A1 under S standard gas; 2 H in S standard gas 2 The S concentration x is the horizontal axis, and the response value y of the gas sensor A1 is the vertical axis. 2 S concentration-response value standard curve, such as Fig.17 As shown, the fitted relationship is y = 0.0004x 3 -0.0481x 2 +1.8348x-5.3459, R 2 =0.9921.

[0215] Application Example 3

[0216] Different ratios of H 2 S was mixed with air to prepare H 2 S standard gas, a voltage of 0.3 V was applied to the gas sensor A1 obtained in Example 1 using a power supply, and then the above concentrations of H 2 After the S standard gas comes into contact with the charged three-dimensional graphene / metal oxide composite ball, the resistance value of the gas sensor A1 is measured, and then the H concentrations of different concentrations are calculated. 2 The response value of gas sensor A1 under S standard gas; 2 H in S standard gas 2 The S concentration x is the horizontal axis, and the response value y of the gas sensor A1 is the vertical axis. 2 S concentration-response value standard curve, such as Fig.18 As shown, the fitted relationship is y = 0.00001x 3 -0.0012x 2 +0.0459x-0.1336, R 2 =0.9987.

[0217] It can be seen from the above results that the gas sensor obtained by the present invention has the advantages of fast response speed to hydrogen sulfide and low power consumption, and can be used to detect H in gas. 2S concentration, has a significantly better effect.

[0218] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A gas sensor, characterized in that: The gas sensor comprises a ceramic package (1) and a three-dimensional graphene / metal oxide composite ball (2) suspended in a groove (11) of the ceramic package (1), and the three-dimensional graphene / metal oxide composite ball (2) is connected to a pin (12) of the ceramic package (1) via a wire; The three-dimensional graphene / metal oxide composite sphere (2) comprises a graphene sphere and a metal oxide supported on the graphene sphere; The specific surface area of ​​the three-dimensional graphene / metal oxide composite sphere is 50-500m 2 / g.

2. The gas sensor according to claim 1, characterized in that The three-dimensional graphene / metal oxide composite spheres have a multi-level pore structure with an average pore diameter of 0.1-50 nm; Preferably, the diameter of the three-dimensional graphene / metal oxide composite sphere is 0.5-5 mm.

3. The gas sensor according to claim 1 or 2, characterized in that: The metal oxide is selected from one or more of WO3, CuO, ZnO, Co3O4, MoO3 and SnO2.

4. The gas sensor according to any one of claims 1 to 3, characterized in that: The preparation method of the three-dimensional graphene / metal oxide composite sphere (2) comprises the following steps: (1) mixing graphene oxide, sodium alginate and water, and then performing ultrasound and heating to obtain a mixed dispersion; (2) The mixed dispersion was dropped into a solution containing Ca by a syringe pump. 2+ soaking the graphene oxide / sodium alginate hydrogel in an aqueous solution to obtain graphene oxide / sodium alginate hydrogel, and washing the graphene oxide / sodium alginate hydrogel to obtain graphene oxide spheres; (3) mixing the graphene oxide beads, metal salt and water to obtain a mixture; (4) subjecting the mixture to a hydrothermal reaction, and then sequentially subjecting the mixture to solid-liquid separation, washing, freeze-drying and sintering.

5. The gas sensor according to claim 4, characterized in that: In step (1), the weight ratio of the graphene oxide, sodium alginate and water is 1-15:0.1-50:1000, preferably 5-10:0.1-40:1000.

6. The gas sensor according to claim 4 or 5, characterized in that: In step (1), the ultrasonication time is 10-120 min.

7. The gas sensor according to claim 4, characterized in that: In step (1), the heating conditions include: temperature of 70-95°C and time of 3-6h.

8. The gas sensor according to claim 4, characterized in that: In step (2), in step (2), the flow rate of the syringe pump is 10-200 μL / min.

9. The gas sensor according to claim 4 or 8, characterized in that: In step (2), the Ca 2+ Ca in aqueous solution 2+ The concentration is 1-10% by weight.

10. The gas sensor according to claim 4, characterized in that: In step (2), the soaking time is 1-24 hours.

11. The gas sensor according to claim 4 or 10, characterized in that: In step (2), the washing process includes: rinsing the graphene oxide / sodium alginate hydrogel with water, and then soaking it in water for 12-48 hours.

12. The gas sensor according to claim 4, characterized in that: In step (3), the metal salt is selected from one or more of tungstate, copper salt, cobalt salt, zinc salt, molybdate and tin salt; Preferably, the metal salt is selected from one or more of sodium tungstate, copper sulfate, zinc nitrate, cobalt nitrate, ammonium molybdate and stannous chloride.

13. The gas sensor according to claim 4 or 12, characterized in that: In step (3), the weight ratio of the graphene oxide beads, the metal salt and the water is 1:1-20:2000-2600.

14. The gas sensor according to claim 4, characterized in that: In step (4), the hydrothermal reaction is a microwave hydrothermal reaction; Preferably, the conditions of the microwave hydrothermal reaction include: temperature of 150-220° C., time of 0.5-6 h, and microwave power of 400-800 W.

15. The gas sensor according to claim 4, characterized in that: In step (4), the freeze-drying conditions include: temperature of 25-60°C and time of 12-48h.

16. The gas sensor according to claim 4, characterized in that: In step (4), the sintering conditions are: temperature of 200-700° C., time of 1-5 h, and inert atmosphere.

17. Use of the gas sensor according to any one of claims 1 to 16 in detecting H2S concentration in gas.

18. A method for detecting H2S concentration in gas, characterized in that: The method comprises the following steps: applying voltage to the gas sensor, then introducing the gas to be tested to contact the three-dimensional graphene / metal oxide composite sphere (2), and determining the concentration of H2S by measuring the response value after contact; The gas sensor is the gas sensor described in any one of claims 1-16.

19. The method according to claim 18, characterized in that The voltage is 0.1-15V.

Citation Information

Patent Citations

  • Graphene / sodium alginate globules modified by nano zero-valent iron and preparing method and application thereof

    CN105668757A

  • Micro-nano sphere-graphene gas sensor and preparation method thereof

    CN105891263A

  • Quick and controllable preparation method of three-dimensional graphene microspheres for adsorption

    CN109896519A

  • Gas sensor, manufacturing method and gas detection method

    CN114518389A

  • Gas sensing nano composite material as well as preparation method and application method thereof

    CN115165977A

Cited By

  • Alginate-based high-entropy metal oxide as well as preparation method and application thereof

    CN121431614A